Wings of fire. Book six, Moon rising : the graphic novel - Deutsch, Barry; Swirsky, Rachel (Graphix, 2023)
When Moonwatcher, a young NightWing with secret powers, begins school at the academy started by the dragonets of destiny after the end of the war, she soon realizes that someone is attacking the students. Moon must choose whether to help or continue to hide her gifts.